Analisis Kadar Alkaloid Ekstrak Dan Fraksi Biji Trembesi (Samanea saman Merr.) Berdasarkan Kepolaran Pelarut Menggunakan Spektrofotometri UV-Vis - Raihan Ahista Qolbi; Yunita Al Azzahra (Journal of Pharmaceutical and Sciences, 2026)
Samanea saman (Merr.) seeds are plant parts that have not been extensively studied, despite their potential as a source of bioactive compounds, particularly alkaloids. Alkaloid compounds are known to possess various pharmacological activities, such as antimicrobial, anticancer, and analgesic effects, making them promising candidates for the development of natural medicines. This study aimed to analyze the alkaloid content in the extract and fractions of S. saman seeds using solvents with different polarity levels,namely n-hexane (non-polar), ethyl acetate (semi-polar), and distilled water (polar). Extraction was carried out using the Ultrasound Assisted Extraction (UAE) method, while quantitative analysis of alkaloid content was performed using UV-Vis spectrophotometry with caffeine as the standard solution. Qualitative testing showed that the ethyl acetate and aqueous fractions were positive for alkaloids. Quantitative analysis of the extract revealed that S. saman seed extract contained alkaloids at a concentration of 142.59 mgCE/g extract. Further analysis of the fractions indicated that the ethyl acetate fraction had the highest alkaloid content 77.34 mgCE/g fraction, compared to the aqueous fraction 24.65 mgCE/g fraction and the n-hexane fraction 45.7 mgCE/g fraction. These findings suggest that semi-polar solvents are the most effective for extracting alkaloid compounds from S. saman seeds, thereby highlighting their potential for further development as raw materials for phytopharmaceuticals or natural-based herbal preparations.